Study of Seasonal Variation on Essential Oil Content and Constituents of Eucalyptus (Eucalyptus globulus) in Three Zones of Kermanshah Province - M Gerdakaneh; N Mohammadi; I Arji (Institue of Medicinal Plants, ACECR, 2018)
Background: Eucalyptus globulus is one of the aromatic and medicinal plants belong to Myrtaceae family. The main combination of essential oil of this plant contains 1-8 Cineole with many medicinal properties. Objective: The effect of harvesting time and location on the essential oil content and composition of eucalyptus (Eucalyptus globulus) leaves. Methods: This experiment was conducted in three regions of Kermanshah province (SarPol-e Zahab, Qasr-e Shirin and Gilan-e Gharb) and four seasons (spring, summer, autumn and winter) on factorial experiment in the base of randomized complete block design with three replications in 2014- 2015. The leaves essential oil extracted by hydrodistillation and its qualitative and quantitative analyses of oils were performed by gas chromatography (GC) and gas chromatography coupled to mass spectrometry (GC/MS). Results: The effect of regions and harvesting time on the essential oil content and component of eucalyptus was significant at 1% level. So that the highest number of constituents (39 Compounds) of the oils and the highest amount of the main ingredients 1,8 cineoles, alpha-pinen, alpha terpinen were observed in Qasr-e Shirin and Gilan-e Gharb area in the summer.  Conclusion: The harvesting time was one of the most important factors influencing the amount of active ingredient of medicinal plants and the highest emount of essential oils and main componds of eucalyptus was obtained in summer.